Genetic Characterization of a Cell Envelope-Associated Proteinase from Lactobacillus helveticus CNRZ32 - Pederson, Jeffrey A. (American Society for Microbiology, 1999)
A cell envelope-associated proteinase gene (prtH) was identified in Lactobacillus helveticus CNRZ32. The prtH gene encodes a protein of 1,849 amino acids and with a predicted molecular mass of 204 kDa. The deduced amino acid sequence of the prtH product has significant identity (45%) to that of the lactococcal PrtP proteinases. Southern blot analysis indicates that prtH is not broadly distributed within L. helveticus. A prtH deletion mutant of CNRZ32 was constructed to evaluate the physiological role of PrtH. PrtH is not required for rapid growth or fast acid production in milk by CNRZ32. Cell surface proteinase activity and specificity were determined by hydrolysis of α(s1)-casein fragment 1-23 by whole cells. A comparison of CNRZ32 and its prtH deletion mutant indicates that CNRZ32 has at least two cell surface proteinases that differ in substrate specificity.